A new version of an additive scheme for the prediction of gas chromatographic retention indices of the 211 structural isomers of 4-nonylphenol - Zenkevich, Igor G.; Makarov, Andrew A.; Schrader, Steffi; Moeder, Monika (Journal of Chromatography A, 2009)
Control of environmental pollution by 4-nonylphenols (4-NP) and effective risk assessment concerning these xenoestrogens requires the identification of the individual isomers contained in the technical mixtures of 4-NP. A new approach is presented here which supports the identification of these compounds by a combination of experimentally determined gas chromatographic retention indices ( I) of reference 4-NP isomers and calculated I-values. In addition to experimental indices, the I-prediction algorithm includes a new version of an additive scheme. The I-values of all structural 4-NP isomers are calculated on the basis of experimentally determined indices of a few available 4-NP isomers and the known retention indices of 75 iso-decanes. A mean deviation of ±11 index units between predicted and experimental I-values demonstrates the feasibility of the new approach. The predicted I-values provide information on the structure of 4-nonylphenol isomers in the technical mixture which has not been considered before. Furthermore, a novel line-coding system is proposed to describe the structure of isomeric 4-NPs and to initiate a current database for the endocrine-disrupting 4-nonylphenols.